Nationwide prevalence and incidence study of neuromyelitis optica spectrum disorder in Denmark. (11th December 2018) - Papp, Viktoria; Illes, Zsolt; Magyari, Melinda; Koch-Henriksen, Nils; Kant, Matthias; Pfleger, Claudia Christina; Roemer, Shanu Faerch; Jensen, Michael Broksgaard; Petersen, Annett Evelyn; Nielsen, Helle Hvilsted; Rosendahl, Lene; Mezei, Zsolt; et al.
Abstract : Objectives: To estimate the nationwide population-based incidence, prevalence, and geographical distribution of neuromyelitis optica (NMO) spectrum disorder (NMOSD) in Denmark based on the 2015 International Panel for NMO Diagnosis (IPND) criteria. Methods: We conducted a multicentre, historically prospective study. Data were sourced from the Danish National Patient Registry, the Danish Multiple Sclerosis Registry, departments of neurology, and laboratories providing aquaporin-4 antibody test. Cases were selected based on the 2006 Wingerchuk and the 2015 IPND criteria and were individually validated by an expert panel. Results: We confirmed NMO in 30 cases (2006 criteria) and NMOSD in 56 cases (2015 IPND criteria) between 2007 and 2014. Defined by the 2006 criteria, the incidence of NMO was 0.029 per 100, 000 person-years (95% confidence interval [CI] 0.014–0.051), and the prevalence (aged 16 years and older) was 0.566 per 100, 000 (95% CI 0.370–0.830). Based on the 2015 IPND criteria, the incidence of NMOSD was 0.070 per 100, 000 person-years (95% CI 0.046–0.102), and the prevalence (aged 16 years and older) was 1.09 per 100, 000 (95% CI 0.808–1.440), without regional differences. Conclusions: Our estimates of incidence and prevalence are similar to other Caucasian population–based studies using the 2015 IPND criteria. We found no geographical clustering in Denmark.